Families' digital media use: Intentions, rules and activities. (28th August 2021) - Eichen, Lars; Hackl‐Wimmer, Sigrid; Eglmaier, Marina Tanja Waltraud; Lackner, Helmut Karl; Paechter, Manuela; Rettenbacher, Karoline; Rominger, Christian; Walter‐Laager, Catherine
Abstract: Since digital media such as smartphones, tablets or laptops are available in almost every household in industrialised countries, parents are challenged to integrate them into their everyday family life. To gain more information on parents' mediation of digital media, the relationships between their educational intentions, objectives and their children's use of digital media were investigated in consideration of the children's age. Overall, 150 Austrian parents with children aged one year and a half to six years participated in the study (two groups were formed based on the age of the children: toddlers and preschool children). They filled in a questionnaire on their intentions and rules for their children's use of media. Moreover, the parents provided information concerning their objectives for digital media use and the kind of activities for which their children use interactive digital toys or passive digital media. Results show that parents' intentions of their children's media use is mainly to gain time for household chores or work. Whereas the age of the children does not seem to be of great importance to parents concerning the media regulation, the results for the objectives and activities parents want their children to do with digital media do indeed differ between the two age‐groups. Practitioner notes What is already known about this topic Average households in industrialised countries are well equipped with digital media technologies. Digital media increasingly become a part of young children's living environment. Parents find it necessary to prevent their children from potential negative effects of digital media use and try to implement rules eg, concerning the time spent with media or content restrictions. What this paper adds Parents' intentions for their children's digital media use as well as the rules they apply for the use of digital media do not differ between toddlers and preschool children. Parents' objectives for their children's use of digital media as well as why and for which purpose their children should use interactive digital toys and passive digital media differs between toddlers and preschool children. Implications for practice and/or policy Support is needed for parents on digital media use with toddlers together. Awareness for digital media use in connection to the rules and objectives needs to be created.